The effect of long term thermal exposure on plastics and elastomers - McKeen, Laurence W. (William Andrew, 2014)
Brings together a wide range of essential data on the effect of long term thermal exposure on plastics and elastomers, enabling engineers to make optimal material choices and design decisions
Includes bibliographical references and index
Keywords: TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Elastomers; Plastics; Hitzebeständigkeit; Kunststoff; Thermoanalyse; Polymere; Elastomer